Bioprospecting of Amazon soil fungi with the potential for pigment production - Celestino, Jessyca dos Reis; Carvalho, Loretta Ennes de; Lima, Maria da Paz; Lima, Alita Moura; Ogusku, Maurício Morishi; Souza, João Vicente Braga de (Process Biochemistry, 2014)
The aim of this study was to isolate fungi able to produce pigments. Fifty strains were isolated from the Amazon soil by the conventional technique of serial dilution. Submerged fermentation was performed in Czapeck broth in order to select strains able to synthesise pigments. Five strains were able to produce pigments and were identified by sequencing the rDNA (ITS regions). These fungi were identified as Penicillium sclerotiorum 2AV2, Penicillium sclerotiorum 2AV6, Aspergillus calidoustus 4BV13, Penicillium citrinum 2AV18 and Penicillium purpurogenum 2BV41. P. sclerotiorum 2AV2 produced intensely coloured pigments and were therefore selected for chemical characterisation. NMR identified the pigment as sclerotiorin. In this work, the influence of nutrients on sclerotiorin yield was also studied and it was verified that rhamnose and peptone increased production when used separately. These results indicate that Amazonian fungi bioprospecting is a viable means to search for new sources of natural dyes. © 2014 Elsevier Ltd.
Keywords: Biochemistry; Biotechnology; Pigments; Amazon Soils; Conventional Techniques; New Sources; Optimisations; Penicillium Citrinum; Pigment Production; Serial Dilutions; Submerged Fermentation; Fungi; Aspergillus; Fungi; Penicillium; Penicillium Citrinum; Penicillium Purpurogenum; Penicillium Sclerotiorum